Análisis de la campaña publicitaria con netlife vas más rápido, muy rápido en las redes sociales de netlife dirigida a clientes home y PYMES durante el primer semestre del 2015 en la ciudad de Guayaquil - Morán Vera, Yajaira Jacqueline (2016)
The telecommunications sector is led by three or four brands here in the city of Guayaquil market, there are brands such as Netlife (brand under analysis), Claro, TVCable, PuntoNet, Cnt among others, each pointing to want to win most of the market. As the demand for Internet grows supply makes it almost parallel, as an example are the stands of TVCable promoting their TriplePack, to Netlife with ads on social networks or on television highlighting the speed of service, the different ads by Claro and Cnt offering their internet packages. Today the user or customer has become more demanding when hiring an internet provider, not just watch the price but the quality of service and the image it has in the market, whether in their quest to find the best wrong, he no longer is complicated and what it does is change providers because it has several alternatives to choose from; For this and other reasons large companies that provide these services seek to capture the attention of potential customers at the same time creating strategies to maintain brand image fresh in the minds of consumers. The market has become so competitive in recent years that each month comes a new advertising some internet provider on TV or in social networks and it is just this means that more bets Netlife always looking for interacting with your group and target your niche called gamers (online players); under Comunity Manager strategies you can address a simple image can be viralizar in seconds thanks to the speed of navigation. Each Internet Service Provider is betting offer something special that the other provider does not have, for example there are developments that show low prices, there are plans that include telephony and cable television, there are brands that sell their expertise, and there are others that sell some feature his service as is the Netlife case with one of his last campaigns sells speed to surf the Internet "with………